The Role of Internal Audit in Evaluating Sustainable Performance and its Impact on the Quality of Financial Reports - Alajeli, Emad Hamza Abd; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2022)
This research aims to demonstrate the role of internal audits in evaluating sustainable performance and its impact on financial report quality using the balanced scorecard. It also drew the internal auditors’ attention in industrial companies to the importance of evaluating sustainable performance and its influence on financial report quality. The researchers used the parallel scorecard to assess the General Company for Automotive and Equipment Manufacturing performance for the years 2017-2020. The General Company for the Production of Automobiles and Equipment and its factories, but not at the required level, and the internal audit of the General Company for the Production of Automobiles and Equipment focuses its work on the economic aspect in a big way and on the traditional financial reports whose data is quantitative and includes cash only. There is also a weakness in the internal audit concerning auditing business and reports prepared by the authorities responsible for the environmental aspect. In light of the conclusions, The researcher made several suggestions, the most important of which are due to the presence of contributions and interests in aspects of sustainable development by the research sample company, so it should prepare sustainable performance reports instead of Traditional financial reports because of the great importance of these reports in reporting all the achievements made by them, whether quantitative or descriptive and thus improving the company’s reputation and image in the community.